"Bodies on Screen: Merging Fat Activism with Feminist Documentary Filmmaking". Issue 2 (3rd May 2020) - Cameron, Layla
ABSTRACT: In the realm of feminist filmmaking, there is often tension in satisfying both the aesthetic demands of visual culture and the political aspects of the subject matter. This is an especially problematic task for work that focuses on fat bodies. Utilizing my experience directing and producing a short documentary film, Fat Hiking Club, this paper explores how fat politics can be integrated into feminist filmmaking. Situated within a feminist media studies framework and using autoethnographic methods, this paper explores some of the topics that need to be addressed at all stages of production in an effort to align media representations with fat activist values.